ONTOLOGICAL ISSUES OF RELIGIOUS WORLDVIEW (Web of Technology: Multidimensional Research Journal, 2024)
The article is devoted to the analysis of ontological issues of religious worldview. It explores social consciousness, religious beliefs and ontological contradictions. The features of ontological analysis and religious worldview are also highlighted.